2021
DOI: 10.1111/jerd.12822
|View full text |Cite
|
Sign up to set email alerts
|

Digital assessment of marginal accuracy in ceramic crowns fabricated with different marginal finish line configurations

Abstract: Aim: To digitally evaluate the marginal adaptation of different types of all-ceramic crowns on two different marginal configurations such as Shoulder and Chamfer of the prepared teeth. Methods:The marginal fit of the crown specimens on the model of the prepared teeth were assessed using the dual scan replica technique. Two plastic teeth were prepared; one having a Shoulder finishing line (A), while the other with a Chamfer finish line (B). Three types of different all-ceramic crowns, layered zirconia, monolith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…20 In terms of marginal fit, Subasi et al 21 revealed no significant difference between the marginal fit of the chamfer finish line and the rounded shoulder finish line when restored with IPS e.max Press or Zirkonzahn. By contrast, Faruqi et al 22 showed that heat-pressed lithium disilicate crowns revealed a better marginal fit than both layered zirconia and monolithic zirconia crowns, and the chamfer finish lines revealed a better marginal fit than the shoulder finish lines. According to clinical studies, the type of finish line has no effect on the clinical outcome of fixed dental prostheses.…”
Section: Discussionmentioning
confidence: 93%
“…20 In terms of marginal fit, Subasi et al 21 revealed no significant difference between the marginal fit of the chamfer finish line and the rounded shoulder finish line when restored with IPS e.max Press or Zirkonzahn. By contrast, Faruqi et al 22 showed that heat-pressed lithium disilicate crowns revealed a better marginal fit than both layered zirconia and monolithic zirconia crowns, and the chamfer finish lines revealed a better marginal fit than the shoulder finish lines. According to clinical studies, the type of finish line has no effect on the clinical outcome of fixed dental prostheses.…”
Section: Discussionmentioning
confidence: 93%
“…The crude death rate among individuals with chronic kidney disease was 134 per 1000 cases. (6)(7)(8)(9)(10)(11)(12) Many times the signs and symptoms are often neglected the early stage and only get medical help when the conditions becomes very severe and sometimes incurable. It is crucial to aware the community about the early signs and symptoms of chronic kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with acyanotic and cyanotic high-flow lesions, as well as those with pulmonary stenosis, should be treated by doctors with a high index of suspicion for the development of pulmonary tuberculosis. (22)(23)(24)(25)(26)(27)(28)(29)(30)(31) Rana Olguntürk, F.Sedef Tunaoğlu, Levent Gökgöz, Leyla Memiş, and Serdar Kula et al reported after seeing clinical improvement, the patient had surgery. The tricuspid valve underwent ringplasty, and the atrial septal defect was repaired.…”
Section: Discussionmentioning
confidence: 99%